Incorporation of GTM and CLT: An Effective Way to Teach (Global Journal of Human-Social Science, 2021)
The two very prominent methodologies are GTM and CLT in the education system in teaching learning English in Bangladesh To show the importance of the combination of these two phenomenal methods is the purpose of this paper In Bangladesh GTM is commonly used for a long time and at present CLT is also a very famous method In this paper the two methods are elaborated clearly in effective teaching and learning of English in Bangladesh The study focuses on GTM and CLT in respects of achieving four skills accuracy fluency teaching-learning process handling the students feelings and emotions the role of the native language of students the language skills that are emphasized and the way of teacher s response to students errors Though CLT is the more beneficial method nowadays GTM also has some positive things to offer Based on the data and findings this paper has also presented some suggestions for effective teaching and learning of English in Bangladesh
Keywords: Grammar Translation Method (GTM; ) Communicative Language Teaching (CLT); Target Language (TL)